Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To show that the equation \( 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) = \sin(4A) \) holds true, let's go through the following trigonometric identities and steps.
1. Double Angle Identities:
[tex]\[ \sin(2A) = 2 \sin(A) \cos(A) \][/tex]
[tex]\[ \cos(2A) = \cos^2(A) - \sin^2(A) \][/tex]
2. Expressing \(\sin(4A)\):
We know:
[tex]\[ \sin(4A) = 2 \sin(2A) \cos(2A) \][/tex]
Since \(\sin(2A) = 2 \sin(A) \cos(A)\) and \(\cos(2A) = \cos^2(A) - \sin^2(A)\), substitute these into the equation:
[tex]\[ \sin(4A) = 2 \left(2 \sin(A) \cos(A)\right) \left(\cos^2(A) - \sin^2(A)\right) \][/tex]
Simplify this:
[tex]\[ \sin(4A) = 4 \sin(A) \cos(A) \left(\cos^2(A) - \sin^2(A)\right) \][/tex]
3. Simplifying Further:
Let's expand the terms:
[tex]\[ \sin(4A) = 4 \sin(A) \left(\cos^3(A) - \cos(A) \sin^2(A)\right) \][/tex]
Distribute \(\sin(A)\):
[tex]\[ \sin(4A) = 4 \sin(A) \cos^3(A) - 4 \sin(A) \cos(A) \sin^2(A) \][/tex]
[tex]\[ \sin(4A) = 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) \][/tex]
Hence, we have shown that:
[tex]\[ 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) = \sin(4A) \][/tex]
Thus, the equation [tex]\( 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) = \sin(4A) \)[/tex] holds true.
1. Double Angle Identities:
[tex]\[ \sin(2A) = 2 \sin(A) \cos(A) \][/tex]
[tex]\[ \cos(2A) = \cos^2(A) - \sin^2(A) \][/tex]
2. Expressing \(\sin(4A)\):
We know:
[tex]\[ \sin(4A) = 2 \sin(2A) \cos(2A) \][/tex]
Since \(\sin(2A) = 2 \sin(A) \cos(A)\) and \(\cos(2A) = \cos^2(A) - \sin^2(A)\), substitute these into the equation:
[tex]\[ \sin(4A) = 2 \left(2 \sin(A) \cos(A)\right) \left(\cos^2(A) - \sin^2(A)\right) \][/tex]
Simplify this:
[tex]\[ \sin(4A) = 4 \sin(A) \cos(A) \left(\cos^2(A) - \sin^2(A)\right) \][/tex]
3. Simplifying Further:
Let's expand the terms:
[tex]\[ \sin(4A) = 4 \sin(A) \left(\cos^3(A) - \cos(A) \sin^2(A)\right) \][/tex]
Distribute \(\sin(A)\):
[tex]\[ \sin(4A) = 4 \sin(A) \cos^3(A) - 4 \sin(A) \cos(A) \sin^2(A) \][/tex]
[tex]\[ \sin(4A) = 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) \][/tex]
Hence, we have shown that:
[tex]\[ 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) = \sin(4A) \][/tex]
Thus, the equation [tex]\( 4 \sin(A) \cos^3(A) - 4 \cos(A) \sin^3(A) = \sin(4A) \)[/tex] holds true.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.